Assessment of community pharmacies readiness to dispense antiretroviral medicines in Rwanda - Cyprien Musafiri; Jean Baptiste Nyandwi; Innocent Hahirwa (Journal of Pharmaceutical Policy and Practice, 2024)
Background: Since the introduction of the ‘Test and treat’ approach in the Human Immunodeficiency Virus (HIV) management, various strategies have been devised and implemented by countries to relieve public health facilities of the large numbers of people coming for medicine refills and clinical follow-up. One of the strategies is the dispensing of antiretroviral medicines through community pharmacies. In Rwanda, community pharmacies are not yet involved in antiretrovirals (ARVs) dispensing, and no study has assessed their readiness to provide this service. This study aimed to assess the readiness of community pharmacy staff and infrastructure to implement a decentralised model of antiretroviral medicines dispensing. Methods: This cross-sectional study included data from 262 community pharmacies sampled across all districts of Rwanda. Primary data were collected using a structured questionnaire, from February to March 2023. Responses were received for 262 community pharmacies, representing the total sample size. Data analysis was done using quantitative descriptive and inferential statistical approaches. Frequency tables and graphs were produced using STATA15 and the outputs were exported to MS Excel as well as MS Word to allow document framing and designing. Results: The research has shown a high proportion of community pharmacy staff trained in HIV prevention (82.4% trained on HIV testing), but a low level of training in treatment (30.5%) and psychosocial support of people living with HIV (29.8%). Infrastructure and storage conditions were found to be adequate, with 99.6% of surveyed Pharmacies having sufficient storage space. Majority (93.9%) expressed their willingness to dispense ARVs in the pharmacy premises. A large number of respondents (92.4%) felt that dispensing of antiretroviral medicines through community pharmacies would lead to an increase in sales of over the counter and other non-HIV related medicines. The main anticipated challenge that should be addressed to ensure effective implementation is the lack of interoperability between reporting systems used by community pharmacies and those used by health facilities providing HIV services (76.7% of respondents). Conclusion: Community pharmacies in Rwanda have majority of staff trained in various areas of HIV prevention, but a small proportion have been trained in HIV care and treatment. Community pharmacies have the necessary infrastructure to dispense ARVs, and those with shortcomings, such as the lack of a separate room for individual patient counselling, are willing to obtain such a room if they are authorised to dispense ARVs. Staffs are willing to dispense ARVs in community pharmacies if the model is recommended by policymakers. The model could have several benefits for community pharmacies and the public health system in general, but there are also challenges that should be mitigated to ensure effective implementation. The staff willingness and expected benefits constitute enabling factors that the Ministry of Health and the national HIV control programme may leverage to prepare for introducing the model of ARVs distribution through community pharmacies.